Management of Chemical Terrorism and Chemical Disasters - Kannan Gajendran Balachandar (International Journal of Disaster Management, 2021)
Though the possibility of terrorist groups obtaining chemical weapons and inflicting mass destruction is relatively low, the relevance of chemical agents remains high since the use of such chemical agents in causing potentially dangerous consequences remains very high. Sporadic chemical attacks and chemical disasters happen all over the world, and they cause long-lasting damages. Easy accessibility to various toxic industrial chemicals and the relatively simple know-how needed to synthesize chemical agents pose a serious threat. However, technological developments and the easy availability of information have empowered the security forces and law enforcement agencies to formulate a responsive mechanism to mitigate the ill effects of chemical disasters. Though the international and national agencies strive hard to ward off the debilitating effects of chemical agents and disasters, such efforts' capability to address the potential risks remains doubtful. This review describes the characteristics and classification of chemical agents and toxic industrial chemicals, their physicochemical properties, detection, decontamination, and response by the security agencies and first responders in addressing the threat to humanity in the form of chemical terrorism and chemical disasters.